L-phenylalanine preloading reduces the 10B(n, α)7Li dose to the normal brain by inhibiting the uptake of boronophenylalanine in boron neutron capture therapy for brain tumours. Issue 1 (1st January 2016) - Watanabe, Tsubasa; Tanaka, Hiroki; Fukutani, Satoshi; Suzuki, Minoru; Hiraoka, Masahiro; Ono, Koji
Highlights: High-dose L-phenylalanine preloading modified the accumulation of L-BPA in BNCT. L-phenylalanine reduced the uptake of L-BPA in the brain relative to the tumour. As a result, L-phenylalanine preloading reduced the irradiated dose of the brain. L-phenylalanine preloading increased the advantage depth of the tumour tissue. L-phenylalanine has advantageous effects on both tumour and the brain doses in BNCT. Abstract: Boron neutron capture therapy (BNCT) is a cellular-level particle radiation therapy that combines the selective delivery of boron compounds to tumour tissue with neutron irradiation. Previously, high doses of one of the boron compounds used for BNCT, L-BPA, were found to reduce the boron-derived irradiation dose to the central nervous system. However, injection with a high dose of L-BPA is not feasible in clinical settings. We aimed to find an alternative method to improve the therapeutic efficacy of this therapy. We examined the effects of oral preloading with various analogues of L-BPA in a xenograft tumour model and found that high-dose L-phenylalanine reduced the accumulation of L-BPA in the normal brain relative to tumour tissue. As a result, the maximum irradiation dose in the normal brain was 19.2% lower in the L-phenylalanine group relative to the control group. This study provides a simple strategy to improve the therapeutic efficacy of conventional boron compounds for BNCT for brain tumours and the possibility to widen the indication of BNCT to various kinds of other tumours.